2016
DOI: 10.1136/bjophthalmol-2016-309418
|View full text |Cite|
|
Sign up to set email alerts
|

Association between VEGF-A and VEGFR-2 polymorphisms and response to treatment of neovascular AMD with anti-VEGF agents: a meta-analysis

Abstract: AimsThe purpose of this study is to investigate whether gene polymorphisms of the vascular endothelial growth factor A (VEGF-A) and its receptor (VEGFR-2) have a pharmacogenetics effect on the anti-VEGF treatment for neovascular age-related macular degeneration (nAMD).MethodsWe carried out a meta-analysis focusing on the relationship between VEGF-related gene polymorphisms and treatment response of nAMD.ResultsFor the single nucleotide polymorphisms (SNPs) within VEGF-A and VEGFR-2, anti-VEGF treatment was muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…VEGFR family members include KDR (kinase insert domain-containing receptor; VEGFR-2), FLT1 (Fms-like tyrosine kinase; VEGFR-1), and FLT4 (VEGFR-3) (51). VEGFR-2 binds VEGF-A, which is expressed in vascular endothelial cells and hematopoietic stem cells (53). In the present study, we focused on VEGFR-2 and its downstream signaling in kaempferol-treated HUVECs.…”
Section: Discussionmentioning
confidence: 96%
“…VEGFR family members include KDR (kinase insert domain-containing receptor; VEGFR-2), FLT1 (Fms-like tyrosine kinase; VEGFR-1), and FLT4 (VEGFR-3) (51). VEGFR-2 binds VEGF-A, which is expressed in vascular endothelial cells and hematopoietic stem cells (53). In the present study, we focused on VEGFR-2 and its downstream signaling in kaempferol-treated HUVECs.…”
Section: Discussionmentioning
confidence: 96%
“…Other researchers are looking for associations between AMD risk alleles and response to anti-angiogenic treatment; one of the studies showed that anti-VEGF treatment was much more effective in patients with nAMD having rs833061 (CC versus TT: OR=2.222, 95% CI 1.252; 3.944, p =0.006; CT versus TT: OR=2.537, 95% CI 1.478; 4.356, p =0.001 and CC versus CT+TT: OR=2.362, 95% CI 1.414; 3.946, p =0.001), [ 69 ]. In addition, newer technologies allow researchers to consider other insights into iPSC-RPE AMD modelling, by adding or eliminating the risk alleles for better response to the treatment [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…After evaluation of nine SNPs (rs699947, rs699946, rs833069, rs833061, rs2146323, rs1413711, rs2010963 and rs1570360 in VEGFA , and rs2071559 in KDR ), anti-VEGF treatment was found to be more effective in patients homozygous for the VEGFA rs833061 minor allele C, compared to the remaining AMD patients (OR = 2.362, 95% CI 1.41–3.95, P = 0.001). This analysis was, however, limited in sample size, including only 444 AMD patients from three independent studies [ 90 ]. An SNP (rs2070296) in the neuropilin-1 ( NRP1 ) gene, encoding the co-receptor for VEGF, has been associated with worse response to treatment in one study [ 91 ], but this SNP has not yet been evaluated in independent cohorts.…”
Section: Current Therapeutic Interventions For Age-related Macular Dementioning
confidence: 99%